Fractions of a chloroform extract of ajenjo leaves (Artemisia mendozana DC. var. mendozana) inhibit the proliferation, viability and clonogenicity of B16-F0 melanoma cells - Millán, María Elisa (2020)
The ajenjo, Artemisia mendozana DC. var. mendozana (Asteraceae), grows in the Andean foothills of Mendoza and San Juan, Argentina, and is used as a medicinal plant for its antispasmodic and antifungal properties. The aim of this work was to obtain fractions of a chloroform extract of ajenjo leaves and to evaluate the in vitro effects on proliferation, viability and clonogenicity of B16-F0 melanoma cells. Using a silica gel chromatography column, 120 fractions were collected and grouped according to the chromatographic profile in 9 main fractions (F1-F9). Their major compounds identified were: Terpenes (F1), terpenes and sesquiterpene lactones (F2-F3), sesquiterpenes (F4-F6) and phenols and sesquiterpenes (F7-9). B16-F0 cells were incubated for 72 h with DMSO (vehicle) or 0.1 mg/ml F1-F9. At 72 h of culture, F1 decreased both the growing index (GI) and cell viability. F2 and F3 both decreased GI and only F3 decreased clonogenic activity. F4 and F5 both decreased GI. Only F5 decreased cell viability and F4 decreased clonogenicity. Consequently, fractions F6-F8 did not affect any of the cell parameters assayed, while F9 decreased cell viability and inhibited clonogenicity.